2017
DOI: 10.3390/diagnostics7030049
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT Findings in a Patient with Chikungunya Virus Infection

Abstract: We present a case demonstrating the diagnostic work-up and follow-up of a patient with Chikungunya infection. An 18F-FDG PET/CT performed four weeks after debut of symptoms revealed pathological 18F-FDG uptake in enlarged lymph nodes on both side of the diaphragm, and inflammation of both shoulder and hip joints. Lymphoma and infection were the main differential diagnoses. Follow-up 18F-FDG PET/CT scan in the patient performed 14 weeks after the abnormal scan, revealed almost complete resolution of the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, this current study confirmed that in DENV, spleen [ 18 F]FDG uptake is still sufficiently sensitive as a possible imaging biomarker for disease and more closely recapitulates the clinical PET/CT observations in DENV patients [ 11 , 12 ]. Aside from DENV and ZIKV, lymphoid tissue [ 18 F]FDG uptake has also been reported in other viral infections, seen in [ 18 F]FDG-PET images of patients infected with chikungunya virus [ 39 ], reactivated Epstein-Barr virus [ 40 42 ], and reactivated varicella zoster virus or shingles [ 43 ]. Lymphoid tissue FDG uptake was also captured in non-human primate models of monkeypox virus infection [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this current study confirmed that in DENV, spleen [ 18 F]FDG uptake is still sufficiently sensitive as a possible imaging biomarker for disease and more closely recapitulates the clinical PET/CT observations in DENV patients [ 11 , 12 ]. Aside from DENV and ZIKV, lymphoid tissue [ 18 F]FDG uptake has also been reported in other viral infections, seen in [ 18 F]FDG-PET images of patients infected with chikungunya virus [ 39 ], reactivated Epstein-Barr virus [ 40 42 ], and reactivated varicella zoster virus or shingles [ 43 ]. Lymphoid tissue FDG uptake was also captured in non-human primate models of monkeypox virus infection [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…High expression of prostaglandins stimulates nociceptors that increase sensitivity to pain and increase osteoclastic activity, resulting in osseous erosion [28]. Additional sites of inflammation include lymph nodes, skin, liver, and spleen [29]. The chronic phase of disease is typically distal, symmetric, and polyarticular, involving the hands, wrists, and ankles [23].…”
Section: Chikungunya Fevermentioning
confidence: 99%
“…Elevated levels of prostaglandins enhance the activation of nociceptors, which heightens pain sensitivity and promotes the activity of osteoclasts, leading to the erosion of bone tissue[28]. Other areas where inflammation may occur include lymph nodes, skin, liver, and spleen[29]. The chronic stage of the illness usually affects the hands, wrists, and ankles in a distal, symmetric, and polyarticular manner[23].…”
mentioning
confidence: 99%